Lower volume throughout the taper and higher intensity in the last interval session prior to a 1500 m time trial improves performance - Spilsbury, K. L.; Fudge, B. W.; Nimmo, M. A.; Faulkner, S. H. (Applied Physiology, Nutrition, and Metabolism, 2021)
Eight highly trained middle-distance runners (1500 m personal best 4:01.4 ± 0:09.2 min) completed two 7-day tapers, separated by at least 3 weeks of regular training: (i) prescribed using prediction models from elite middle-distance runners, where continuous running volume was reduced by 30% and interval intensity was equal to 1500 m race pace (RP); and (ii) continuous running volume was reduced by 60% and intensity of the final interval session was completed at 110% of 1500 m race pace (HI). Performance was assessed using 1500 m time trials on an indoor 200 m track 1 day before, and 1 day after each taper. Performance time was improved after HI by 5.2 ± 3.7 s (mean ± 90% confidence limits, p = 0.03) and by 3.2 ± 3.8 s after RP (p = 0.15). The first and second 300 m segments of the 1500 m time trial were faster post-taper in RP (p = 0.012 and p = 0.017, respectively) and HI (both p = 0.012). Running faster than race pace late in a low-volume taper is recommended to improve 1500 m track performance. A positive pacing strategy is adopted after tapering, although care should be taken to avoid an over-fast start. Novelty: • A large reduction in volume during tapering and an increase in final interval session intensity improves running performance. • Athletes adopt a negative pacing strategy before tapering and a positive-pacing strategy after tapering.